THE INFLUENCE OF MINERAL FEEDING ON SEED PRODUCTIVITY AND SOWING QUALITY OF SEEDS OF ALLIUM PORRUM IN CONDITION OF CENTRAL NONCHERNOSEM ZONE - A. A. Koshevarov; S. M. Nadezhkin; A. F. Agafonov (Овощи России, 2012)
The influence of mineral fertilizers (nitric, phosphoric and potassium) on Allium porrum were evaluated in the trials. Optimum doses and combinations were installed for development of seed plants, receptions of the most output and quality of seed product.